AUTHORITATIVE CARTOGRAPHY IN BRAZIL AND COLLABORATIVE MAPPING PLATFORMS: CHALLENGES AND PROPOSALS FOR DATA INTEGRATION - Silva, Leonardo Scharth Loureiro; Camboim, Silvana Philippi (Boletim de Ciências Geodésicas, 2022)
Brazil has a large area with missing or outdated mapping on the largest scales of its authoritative mapping. The use of data from collaborative mapping platforms appears as an alternative that may contribute to minimizing this problem, either by updating or completing the mapping coverage in Brazil, as proposed or performed by some National Mapping Agencies abroad. The present work aims to analyze a methodology to provide accurate and documented integration of volunteered geographic information and the Brazilian authoritative mapping. The proposal starts with the semantic compatibility between the conceptual models adopted in both official cartography and OpenStreetMap platform. The research continues with the identification of object classes with the most significant potential for integration. Finally, we developed some experiments to evaluate and validate the OSM data integration process in a 1:25,000 scale cartographic database. Even in regions with a recent mapping, the results of the preliminary assessment indicate the potential for an increase of about 52% and 16% of features in the ‘road system’ category, which suggests a very promising method for use in areas with missing or outdated mapping, and its applicability to other categories.